Revisiting the Filipino Value Utang na Loob: Contextual Perceptions, Implications and Inputs to Sustaining the Filipino Psychology Discussions - Rey Marco Z. Casiño; Serrano, Liandro; Granada, Maria Isabel (Ilmu Inovasi Nusantara, 2025)
Utang na loob (debt of gratitude) is a cultural value deeply ingrained in Filipino society. It is not merely a part of the local vernacular but a profound moral construct that serves as one of the pillars of Filipino identity and social reality. However, this concept is often misunderstood and misused in practice, potentially leading to unhealthy social pressures for the recipient. This phenomenon has fostered a perception that utang na loob is burdensome and even considered a toxic trait in social relationships. This study aims to understand the true essence of utang na loob in a localized context and explore how Filipinos perceive and apply this value in their daily lives. A qualitative survey was conducted, employing the In Vivo Coding method to capture the intrinsic meanings embedded in the participants' statements. The collected data were then analyzed and structured into manageable insights that provided a deeper understanding of the concept. The study revealed that utang na loob goes beyond mere reciprocity and serves as a tool for strengthening social connections. However, its misuse can lead to emotional pressure on the recipient, often making them feel bound by an overwhelming social obligation. It is essential to instill in the younger generation that utang na loob should be rooted in goodwill and genuine concern for others rather than being perceived solely as a social obligation that imposes burdens